Global Financial Stability Report, September 2002 : Market Developments and Issues. (Global Financial Stability Report; Global Financial Stability Report ;, 2002)
This September 2002 issue of the Global Financial Stability Report highlights that during the second quarter of 2002, a sharp erosion of investor confidence heightened risk aversion and growing concerns about the strength and durability of the global recovery. The pace and quality of corporate earnings had repercussions in all of the major equity, credit, and foreign exchange markets. Market adjustments occurred against the background of the bursting of the telecom, media, and technology bubble, which exposed a culture of irrational exuberance, and sometimes greed, among many buyers, sellers, and intermediaries.